2000
DOI: 10.1046/j.1523-1755.2000.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemoglobin levels in hemodialysis patients with asymptomatic cardiomyopathy

Abstract: Normalization of hemoglobin does not lead to regression of established concentric LV hypertrophy or LV dilation. It may, however, prevent the development of LV dilation, and it leads to improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
209
0
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 369 publications
(225 citation statements)
references
References 26 publications
7
209
0
9
Order By: Relevance
“…Small studies among dialysis patients also demonstrated benefits of [Hb] normalization on sleep (42), neurologic function (43), exercise capacity, and well being (44,45). Quality of life has also been demonstrated, in a variety of controlled and uncontrolled studies, to be related to [Hb] among dialysis patients (20,45,46). The fact that we were unable to observe a difference in quality of life between groups in this study is likely to be related to the small overall difference in [Hb], rather than an intrinsic difference between dialysis and nondialysis patients.…”
Section: Discussionmentioning
confidence: 97%
“…Small studies among dialysis patients also demonstrated benefits of [Hb] normalization on sleep (42), neurologic function (43), exercise capacity, and well being (44,45). Quality of life has also been demonstrated, in a variety of controlled and uncontrolled studies, to be related to [Hb] among dialysis patients (20,45,46). The fact that we were unable to observe a difference in quality of life between groups in this study is likely to be related to the small overall difference in [Hb], rather than an intrinsic difference between dialysis and nondialysis patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, on balance, among randomized controlled trials of dialysis patients, there has been no demonstration of an impact of normalization of Hgb with ESA on CVD events or survival (20)(21)(22)(23)(24)(25); moreover, many of these studies have raised questions of harm (vascular access thrombosis and stroke), which have not been definitively addressed. Smaller randomized trials among nondialysis patients have also failed to show improvements in surrogate end points for CV outcomes (left ventricular mass index on echocardiography and decline in GFR) among ESA-treated patients (26)(27)(28)(29).…”
Section: Trials Of Hgb Normalization and Cardiovascular Outcomesmentioning
confidence: 99%
“…Anemia in CKD is also associated with diminished survival (5)(6)(7)(8)(9)(10). Managing anemia may reduce the need for recurrent blood transfusions and improve patient-reported physical function and exercise tolerance (1,(10)(11)(12)(13). However, recommendations regarding optimal hemoglobin (Hb) levels in CKD continuously evolve, and results from randomized controlled trials of corrective strategies continue to be mixed.…”
Section: Introductionmentioning
confidence: 99%